ASSESSING IN-HOSPITAL MORTALITY AND PREDICTORS IN PATIENTS WITH CONTRAST-INDUCED NEPHROPATHY FOLLOWING PRIMARY PERCUTANEOUS CORONARY INTERVENTION - Kumar, Rajesh; Mal, Kheraj; Urooj, Abiha; Lohana, Barkha; Rasool, Mohammad; Daud, Muhammad Yousuf; Rahooja, Kubbra; Samad, Maryam; Safdar, Uroosa; Naseer, Ali Bin; Chachar, Kalsoom; Ishaq, Muhammad; et al. (Journal of Ayub Medical College Abbottabad, 2023)
Background: The contrast-induced nephropathy (CIN) is a common complication of primary percutaneous coronary intervention (PCI) it has been reported to be associated with an increased risk of mortality. The study reported the in-hospital mortality among patients who developed CIN after primary PCI. Methods: This descriptive cross-sectional study was conducted on a sample of consecutive who developed CIN after primary PCI at a tertiary care cardiac hospital in Karachi, Pakistan. The CIN was defined as either a relative increase of 25% or an absolute increase of 0.5 mg/dL in post-procedure serum creatinine within 72 hours. The in-hospital mortality status was recorded and clinical and demographic predictors of in-hospital mortality were identified with the help of binary logistic regression analysis. Results: In the study sample of 402 patients, 74.1% (298) were male and the mean age of the study sample was 59.4±11.5 years. The in-hospital mortality rate was 9.7% (39). On multivariable analysis, an increased risk of mortality was found to be independently associated with inferior wall myocardial infarction (IWMI) with right ventricular (RV) infarction, intra-procedure arrhythmias, and pump failure with an adjusted odds ratio of 3.63 [95% CI: 1.31-10.08; p=0.013], 5.53 [95% CI: 1.39-22.06; p=0.015], and 8.94 [95% CI: 3.99-20.02; p<0.001], respectively. Conclusion: In conclusion, there is a high rate of mortality for patients who develop CIN after primary PCI, and the risk of mortality is further aggravated by the presence of IWMI with RV infarction, intra-procedure arrhythmias, and pump failure.